The Effect of Effectiveness Ratio, Efficiency Ratio, and Fiscal Independence on Financial Distress of Local Governments in Regencies and Cities in Indonesia for the 2022-2023 Period - Athaya, Atha; Gamayuni, Rindu Rika (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study aims to examine the effect of effectiveness ratio, efficiency ratio, and fiscal independence on financial distress in local governments of regencies and cities in Indonesia for the 2022-2023 period. Design/methodology/approach – This research uses a quantitative method with secondary data obtained from the audited Local Government Financial Reports (LKPD) and the Fiscal Capacity Index issued by the Ministry of Finance. The analysis was conducted using binary logistic regression. Findings – The results show that the effectiveness ratio has a negative and significant effect on financial distress, while the efficiency ratio has a positive and significant effect. Fiscal independence has a negative and significant effect, indicating that higher autonomy reduces the risk of fiscal distress. Originality – This study provides empirical evidence on how local government financial performance affects fiscal distress by integrating effectiveness, efficiency, and fiscal independence ratios in one model. Keywords: Effectiveness Ratio, Efficiency Ratio, Fiscal Independence, Financial Distress, Local Government. Paper type Research Result